(untitled) (IAHS Medical Journal, 2025)
Background: Acne is a common inflammatory skin disease which affects the pilosebaceous units of the skin. It can have severe psychological effects and can leave the patient with severe skin scarring. In this study physical therapies of acne treatment like come done, extraction, cryoslush therapy, cryotherapy, electrocauterization, intralesional corticosteroids and optical treatments the safety and efficacy of comedone extraction with incision and drainage in nodulo cystic acne are mentioned. Materials and methods: A descriptive study was conducted at Lab Aid Diagnostic Ltd, Jashore, from January to June 2024. A total of 200 respondents were included in the study. Data were collected through structured interviews and medical record reviews. Results: The overall proportion of Acne Vulgaris among rural male 52.5% and female were 47.5%. The proportion is varied by the age group, 31% in aged 11-15 years, 35% in aged 16-20 years, 12.5% in aged 21-25 years, 7.5% in aged 26-30 years, 6.5% in aged 31-35 years and rest 7.5% aged >35 years. About the educational status, 1.5% completed primary level, 31% completed secondary level, 35% higher secondary level and rest 32.5% completed graduation. According to occupational status, 32.5% were employed and 67.5% were unemployed. Among 200 respondents, 25% were from low socio-economic status, 35% from middle income family and 40% from high income status. According to nutritional status 20%, were underweight (BMI < 18.5), 45% had Normal weight (BMI 18.5-24.9) and 35% overweight (BMI ≥ 25). Association between duration of complete cure and grades of acne vulgaris after only physical extraction like Comedon extraction and incision and drainage in nodulo-cystic acne shows significant association (P < 0.0006). The association between Gender and grades of acne vulgaris shows significant association (P< 0.0028). Association between socioeconomic status and grades of acne vulgaris shows significant association (P< 0.05). Conclusion: This study highlights the safety and efficacy of comedone extraction with incision and drainage in nodulo cystic acne without any scarring and short period of time was taken for complete cure. IAHS Medical Journal Vol 7(2), December 2024; 83-86